2022
DOI: 10.4103/ijabmr.ijabmr_637_21
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nurses’ Ethical Reasoning with the Quality of Nursing Care

Abstract: Context A high quality of nursing care is an important priority of nursing profession and directly associated with increased patient satisfaction. Evidence shows that ethical professional issues are challenging with significant influences on the quality of nursing care. Aims The aim of this study was to determine how quality of patient care relates to the nurses’ ethical reasoning as viewed by patients in medical wards. Settings and Design Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Also, our results indicated that there was a significant positive relationship between SI and the caring behavior of nurses working in the emergency department, which was in agreement with the study of Sunaryo et al (2018) suggesting the positive association between SI and caring behavior ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Also, our results indicated that there was a significant positive relationship between SI and the caring behavior of nurses working in the emergency department, which was in agreement with the study of Sunaryo et al (2018) suggesting the positive association between SI and caring behavior ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…In their study, Sonaryo et al (2018) found that both emotional intelligence and SI had a direct effect on caring behavior. On the other hand, SI had an indirect effect on caring behavior via the mediating role of job burnout, which was in line with our study ( 44 ). According to the results of the present study, ethical reasoning playing the mediating role in the relationship between SI and the caring behavior of nurses was revealed using the SEM.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations